Teknik Penerjemahan Kejadian 1-2 dalam Alkitab Terjemahan Baru Indonesia Edisi Kedua - Steven (STT Reformed Injili Internasional, 2024)
Translation of the Old Testament from Hebrew-Aramaic into other languages always raises textual issues. In the context of the Indonesian Bible, these textual issues have not received sufficient academic attention. With the release of the second edition of the New Translation Bible (TB2) in 2023, this paper will review the translation techniques of TB2 using textual criticism methods on a sample of Genesis 1-2. The first edition of the New Translation Bible (TB) will also be compared, along with the Masoretic Text (MT) and the Septuagint (LXX) where necessary. The findings are as follows: (1) TB2 shows consistency in word equivalence with MT, (2) TB2 includes a literal translation of MT, and (3) where verses are not problematic, TB2 appears to reflect MT more accurately as the Vorlage. It is hoped that this article will contribute insights into Bible translation techniques in Indonesian for the future.